Civilian oversight of policing : governance, democracy and human rights - Goldsmith, Andrew John; Lewis, Colleen (Oxford ; Portland, Oregon : Hart Publishing, 2000)
"How the police are policed is no longer just a domestic issue. The involvement of police, and other security forces, in systematic abuses of human rights in many developing countries, as well as in so called developed countries, has placed the control of police on a number of international agendas. More and more countries are experimenting with different forms of police accountability and many are turning to civilian oversight bodies in an attempt to improve the process. This book examines recent experiences with, and prospects for, civilian oversight. It looks at how this relatively new method of police accountability has been interpreted and implemented in a wide range of jurisdictions around the world. While looking at recent experiences in countries which have used the civilian oversight process for some years (the United States of America, United Kingdom, Northern Ireland and Australia), it also looks at recent attempts to establish civilian oversight bodies in South Africa, Israel, Central and South America and Palestine."--Provided by publisher
The politics of civilian oversight: serious commitment or lip service? / Colleen Lewis -- Race, democracy and law: civilian review of police in Washington D.C. / Cheryl Beattie and Ronald Weitzer -- Back to the future: the death of civilian review of public complaints against the police in Ontario, Canada / Tammy Landau -- Instituional structure vs political will: Albuquerque as a case study in the effectiveness of citizen oversight of the police / Eileen Luna and Samuel Walker -- Evaluating the performance of external oversight bodies / David Brereton -- Evaluating the new civilian complaints board in Israel / Sergio Herzog -- Evaluating police complaints legislation: a suggested framework / Philip Stenning -- Police accountability reform in Colombia: the civilian oversight experiment / Andrew Goldsmith -- South African Independent Complaints Directorate / Bronwen Manby -- Confronting a culture of impunity: the promise and pitfalls of civilian review of police in Latin America / Rachel Neild -- Accountability and police complaints in Northern Ireland: leaving the past behind? / Mary O'Rawe and Linda Moore -- Called to account: civilian oversight in the Palestinian context / Beverly Milton-Edwards.
Includes bibliographical references and index.
Online resource; title from e-book title screen (EBL platform, viewed April 4, 2016).
Keywords: Police -- Complaints against; Police administration -- Citizen participation; Police-community relations; Civilian review boards (Police administration)